2021
DOI: 10.3390/computers10050064
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Performance and Response Latency Measurements of Linux Kernels on Single-Board Computers

Abstract: This research performs real-time measurements of Linux kernels with real-time support provided by the PREEMPT_RT patch on embedded development devices such as BeagleBoard and Raspberry Pi. The experimental measurements of the Linux real-time performance on these devices are based on real-time software modules developed specifically for the purposes of this research. Taking in consideration the constraints of the specific hardware platforms under investigation, new measurements software was developed. The measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Some make a timing analysis of virtualized environments [8,24,25], others analyze the interrupt latency on an OS [26,27], and others analyze the interrupt latency on virtualized environments [28][29][30][31][32][33]. Finally, some propose new tools for analyzing latencies in embedded systems [34][35][36][37][38].…”
Section: Related Workmentioning
confidence: 99%
“…Some make a timing analysis of virtualized environments [8,24,25], others analyze the interrupt latency on an OS [26,27], and others analyze the interrupt latency on virtualized environments [28][29][30][31][32][33]. Finally, some propose new tools for analyzing latencies in embedded systems [34][35][36][37][38].…”
Section: Related Workmentioning
confidence: 99%
“…2. The reason for using an MCU between the ADC and SBC is to guarantee that certain quick periodic or random events on the signals are sampled in time [20]. For example, the SBC is capable of running Linux, which brings some benefits but also results in some limitations.…”
Section: A Hardware and Data Acquisition Designmentioning
confidence: 99%
“…He demonstrated that the PREEMPT_RT patch overall improves the Linux kernel real-time performance compared to the standard one. The reduced worst-case latencies on such devices running Linux with real-time support could make them potentially more suitable for real-time applications as long as a latency value of about 160 μs, as an upper bound, is an acceptable safety margin [29].…”
Section: Related Workmentioning
confidence: 99%